Living Cationic Ring-Opening Polymerization of Hetero Diels–Alder Adducts to Give Multifactor-Controlled and Fast-Photodegradable Vinyl Polymers - Chae, Ju Hyung; Choi, Minyeong; Son, Semin; Ko, Su Min; Lee, In Hwan (Angewandte Chemie - International Edition, 2023)
Precise control of multiple structural parameters associated with vinyl polymers is important for producing materials with the desired properties and functions. While the development of living polymerization methods has provided a way to control the various structural parameters of vinyl polymers, the concomitant control of their sequence and regioregularity remains a challenging task. To overcome this challenge, herein, we report the living cationic ring-opening polymerization of hetero Diels–Alder adducts. The scalable and modular synthesis of the cyclic monomers was achieved by a one-step protocol using readily available vinyl precursors. Subsequently, living polymerization of the cyclic monomers was examined, allowing the synthesis of vinyl polymers while controlling multiple factors, including molecular weight, dispersity, alternating sequence, head-to-head regioregularity, and end-group functionality. The living characteristics of the developed method were further demonstrated by block copolymerization. The synthesized vinyl polymers exhibited unique thermal properties and underwent fast photodegradation even under sunlight.
Keywords: Alternating; Cationic ring opening polymerization; Cyclic monomers; Hetero-Diels-Alder adducts; Multi-factor; Photo degradation; Regioregularity; Ring opening; Structural parameter; Vinyl polymer; Alternating; Hetero Diels–Alder Adduct; Living Polymerization; Photodegradation; Ring-Opening